A Study of Basic Military Training on the Physical Fitness and Physical Self-Concept for Cadets: 入伍訓練對軍校新生體適能及自我身體概念的研究 - CHEN, Kenny Wen Chyuan; CHIU, Pin Kun; LIN, I An; XU, Ku Fu; HSU, Mei Chich; LIANG, Michael Tian Chong (Asian Journal of Physical Education & Recreation, 2007)
LANGUAGE NOTE | Document text in English; abstract also in Chinese. This study investigated the physiological and psychological aspects of first-year cadets who adopted a basic military training. We focused on the extent to which the Military physical fitness and the physical self-concept will be affected by a basic military training program. Military physical fitness included the score of BMI, pull-ups, 3000m endurance running and 1-min sit-up. Physical self-concept was assessed using the Marsh's Physical Self-Description Questionnaire (PSDQ), which was adapted to use in college students. PSDQ scale was assessed using a 6-point rating scale on which the subject estimated their physical characteristics. Testing was administered in a pre- and posttest fashion over 9 weeks (n=166). The collected data were analyzed by t-test. The study revealed that 1) Military physical fitness that including 3000m endurance running, 1-min sit-up and BMI are significant (p<.05), (2) total score of PSDQ assessment are non-significant (p>.05), (3) the health of PSDQ are significant (p<.05), (4) the physical activity of PSDQ are significant (p<.05). Results show that physical fitness and psychological measurement are really affected by basic military training program such that cadets have a more positive health and better body conditions due to basic military training. 本研究的主要目的在於研究軍校新生在經過入伍訓練後其生理與心理方面的變化。我們研究主要焦點在於入伍訓練課程能否影響軍方體適能和身體自我概念，而軍中體適能的項目包含：拉單槓、3000公尺耐力跑、一分鐘仰臥起坐，身體自我概念的評估則是將Marsh的身體自我描述問卷(PSDQ)改編成適合大專學生適用的量表。PSDQ的評估使用六點等級讓受試者來評估自己的身體特點。測試分別在9周入伍訓練的前後實施(共166人)。收集到的資料以成對樣本T考驗檢定。本研究的結果呈現(1)軍方體適能中的3000公尺耐力跑，一分鐘仰臥起坐和BMI皆有顯著的變化(p<.05) (2) PSDQ的總得分並未變化(p>.05) (3) PSDQ的健康分項得分有顯著差異(p<.05) (4) PSDQ的身體活動分項得分有顯著差異(p<.05)。結果顯示體適能和心理方面的測量確實受到入伍訓練的影響，所以軍校生會因為入伍訓練而有更積極正向的健康概念與較佳的身體狀況。